Sleep Latency and Post-Traumatic Stress Disorder Among Retired Career Florida Firefighters: Evidence From the Advancing Epidemiology of Retired Firefighters Aging Longitudinally Cohort. Issue 12 (7th December 2022) - Testoff, Addison C.; Schaefer Solle, Natasha; Shafazand, Shirin; Louzado-Feliciano, Paola; Lee, David J.; Koru-Sengul, Tulay; Kobetz, Erin N.; Caban-Martinez, Alberto J.
Abstract : Among retired career Florida firefighters, approximately 8.0% screened positive for PTSD risk, 37.6% had prolonged sleep latency (≥20 minutes to fall asleep), 23.7% use sleeping pills, and 39.3% spoke to a health professional about trouble sleeping. Diagnosed sleeping disorders included sleep apnea (24.0%), insomnia (2.8%), and restless leg syndrome (2.4%). Abstract : Objective: Our objective was to estimate the association of post-traumatic stress disorder (PTSD) and sleep latency among retired firefighters. Methods: Baseline health survey data collected from retried career Florida firefighters participating in an ongoing prospective cohort study from 2017 to 2021 were analyzed. Risk for PTSD was assessed using a four-item primary care PTSD screening construct, and sleep onset latency was assessed by self-reported length of time to fall asleep. Results: Among the 500 participants, 8.0% screened positive for PTSD risk and 37.6% had prolonged sleep onset latency (≥20 minutes to fall asleep). Retired firefighters with PTSD risk were 2.7 times more likely (adjusted odds ratio, 2.70; 95% confidence interval, 1.27–5.75) to have prolonged sleep latency compared with those without PTSD risk while controlling for covariates. Conclusions: Retired firefighters who screen positive for PTSD risk are three times more likely to report delayed sleep onset latency.